Means of Implementing Negative Representation of “Others” Strategy as Markers of G. Bush Jr. and B. Obama’s Conceptual Styles - Kalishchuk, Diana (East European Journal of Psycholinguistics, 2017)
The article deals with the speech manipulation as a means of expression of persuasiveness in discourse. Manipulation is treated as a peculiar communicative-speech strategy to influence the addressee in the political discourse, which is implemented through a set of tactics. The selection of tactics is greatly affected by the conceptual style of the author of political discourse. The article deals with the analysis of the tactics, through which the strategy of negative presentation of “others” is realized, namely, the tactics of “Super-Generality” and “Exemplification”. These tactics are treated as the markers of conceptual styles of the USA Presidents G. Bush Jr. and B. Obama. It has been proved, the speech peculiarities of persons with different conceptual styles predetermine higher frequency of some tactics and, consequently, lower frequency of other tactics. The tactics of “Exemplification” consists in transferring the features, which generally characterize some specific ethnic (or other) group onto the certain individual or the single event. This tactics may be considered to be typical for the discourse of G. Bush Jr., whose conceptual style is analytical. It is caused by such characteristics of the speech of persons with analytical style as deductiveness and the tendency to the excessive use of labels. Inductiveness of B. Obama’s speech whose conceptual style is relational, explains higher frequency of the tactics of “Super-Generality” in his discourse. The tactics of “Super-Generality” consists in generalizing some unitary model, some aspects of unitary experience to soma group scheme. References Бережанська Ю. В. Лінгвостилістичні особливості персуазивного медичного дискурсу, присвяченого проблемі евтаназії // Наукові записки Національного університету «Острозька академія». Серія «Філологічна»: зб. наук. праць. 2014. Вип. 44. С. 39–41. Berezhanska, Yu. (2014). Linhvostylistychni osoblyvosti persuazyvnoho medychnoho dyskursu, prysvyachenoho problemi evtanasii [Linguo-stylistic peculiarities of medical discourse dedicated to the issue of eutanasia]. Naukovi Zapysky Natsionalnoho Universytetu “Ostroz’ka Academia”, 44, 39–41. Голоднов А. В. Лингвопрагматические особенности персуазивной коммуникации (на примере современной немецкоязычной рекламы). Автореф. дис. ... канд. филол. наук: 10.02.01. СПб., 2003. Golodnov, A. V. (2003) Lingvopragmaticheskiye osbennosti persuazivnoy kommunikatsii (na primere sovremmennoy nemetsoyazychnoy reklamy) [Lingvopragmatic peculiarities of persuasive communication (based on the German-speaking advertisements)]. Extended Abstarct of Ph.D. dissertation. St. Petersburg. Дейк Т. А. ван. Дискурс и власть: Репрезентация доминирования в языке и коммуникации/ Т. А. ван Дейк ; [пер. с англ.]. М.: Книжный дом «ЛИБРОКОМ», 2013. Dijk, T. van. (2013). Diskurs i Vlast’: Reprezentatsiya Domimirovaniya v Yazyke i Kommunikatsiyi [Discourse and Power: Representation of Dominance in the Language and Communication]. Moscow: Librokom. Доценко Е. Л. Психология манипуляции: феномены, механизмы и защита. СПб.: Речь, 2004. Dotsenko, Ye. (2004). Psikhologiya manipuliatsiyi: fenomeny, mekhanizmy i zashchita [Psychology of manipulation: phenomena, mechanisms and protection]. St. Petersburg: Rech’. Засєкіна Л. В., Засєкін С. В. Психолінгвістична діагностика. Луцьк: РВВ «Вежа», 2008. Zasiekina, L., Zasiekin, S. (2008). Psycholinhvistychna Diahnostyka [Psycholinguistic Diagnostics]. Lutsk: Vezha”. Ильченко М. Л. Метакоммуникативные тактики доминирования в американском электоральном дискурсе (на материале предвыборных теледебатов) // Проблемы лингвистики и лингводидактики. Вып. 1. Под ред. С. А. Моисеевой, Л. Г. Петровой. Белгород: ИПЦ «ПОЛИТЕРРА», 2013. С. 88–96. Ilchenko, M. (2013). Metakommunikativnyie taktiki dominirovaniya v amerakanskom electoralnom diskurse (na materiale predvybornykh teledebatov) [Metacommunicative tactics of domination in American electoral discourse (based on pre-election debates)]. Problemy Lingvistiki i Lingvodidaktiki, 1, 88–96. Калита А. А., Тараненко Л. И. Речевая манипуляция: определение, функция, механизм реализации // Вісник Харківського національного університету імені В. Н. Каразіна. Серія «Романо-германська філологія. Методика викладання іноземних мов». 2012. № 1022. Вип. 71. С. 10–19. Kalyta, A., Taranenko, L. (2012). Rechevaya manipulyatsiya: opredeleniye, funktsiya, mekhanizm realizatsii [Speech manipulation: definition, function, mechanisms of realisation]. Bulletin of V. Karazin National University of Kharkiv, 71(1022), 10–19. Молодыченко Е. Н. Создание образа врага как персуазивная стратегия американского политического дискурса: когнитивный и лингвопрагматический анализ: на материале публичных речей политических деятелей 1960–2008 гг: Автореф. дис. … канд. филол. наук: 10.02.04. С.-Петербург, 2010. Molodychenko, Ye. (2010). Sozdaniye obraza vraga kak persuazivnaya strategiia amerikanskogo politicheskogo diskursa: kognitivnyy i lingvopragmaticheskii analiz: na material publichnykh rechey politicheskikh deyateley 1960–2008 [Enemy Image Creation as Persuasive Strategy of American Political Discourse: Cognitive and Lingual-Pragmatic Analysis: Based on Public Speeches of Politicians of 1960–2008]. Extended Abstract of Ph.D. dissertation. St. Petersburg. Серажим К. С. Дискурс як соціолінгвальне явище: методологія, архітектоніка, варіативність (на матеріалах сучасної газетної публіцистики): монографія / за ред. В. Різуна)]. Київ, 2002. Serazhym, K. (2002). Dyskurs Yak Sotsiolinhvalne Yavyshche: Metodolohiya, Arkhitektonika, Variatyvnist’ (Na Materialakh Suchasnoii Hazetnoii Publitsystyky) [Discourse as Sociolingual Phenomenon: Methodology, Archirectonics, Variability (Based on Modern Newspaper Discourse)], V. Rizun, ed. Kyiv. Чернявская В. Е. Дискурс власти и власть дискурса: проблемы речевого воздействия: учеб. пособие. М.: Флинта; Наука, 2006. Chernyavskaya, V. (2006). Diskurs Vlasti i Vlast’ Diskursa: Problemy Rechevogo Vozdeystviya [Discorse of Power and Power of Discourse: Issues of Speech Influence]. Moscow: Flinta; Nauka. Cohen, R. (1969). Conceptual styles, culture conflict, and nonverbal tests of intelligence. American Anthropologist, 71(5), 828–856. Sources Nation and World. Transcript of President George W. Bush’s «Mission Accomplished» Speech. Retrieved from: http://pix11.com/2013/04/30/transcript-of-president-george-wbushs-mission-accomplished-speech/#axzz2k5GVjca0 President Bush Discusses the Middle East. July 16, 2007. Retrieved from: https://2001- 2009.state.gov/p/nea/rls/rm/2007/ 88506.htm President Obama’s Full Campaign Kickoff Speech. May 05, 2012. Retrieved from: http://articles.latimes.com/2012/may/05/news/la-pn-transcript-obama-campaign-kickoff20120505 Statement by the President on Ukraine. July 18, 2014. Retrieved from: http://www.whitehouse.gov/the-press-office/2014/07 /18/statement-president-ukraine State of the Union Address. January 23, 2007. Retrieved from : http://millercenter.org/president/speeches/detail/4455 State of the Union 2012: Obama Speech Transcript. January 25, 2012. Retrieved from: http://www.washingtonpost.com/politics/state-of-the-union-2012-obama-speechexcerpts/2012/01 /24/gIQA9D3QOQ_story.html War and Appeasement. Barack Obama Speech on Bush, McCain, War and Appeasement in Watertown, South Dakota. 2008. Retrieved from: http://irregulartimes.com/ index.php/archives/2008/05/16/text-transcript-of-barack-obama-speech-on-bush-mccainwar-and-appeasement-in-watertown-south-dakota-on-may-16-2008/